Assessment of the geographical service Area of Friday mosques in the city of Buraydah using site location allocation models and spatial interpolation techniques - Alqasim, Rawan Mosa Ibrahim; Alshwesh, Ibrahim Obaid (Journal of Humanities & Social Sciences, 2022)
This study analyses the spatial distribution of Friday mosques in Buraydah neighbourhoods using geographic information systems including the spatial distribution technique of Dasymetric Mapping to reveal population distribution, and the Location Allocation Model P-Median to study the current mosque sites and their service coverage. The study recommends optimal sites by applying one of the criteria for spatial requirements, which includes the scopes of service (450 m and 800 m). The study concludes that in current mosque locations, the percentage of the city’s population outside the area of service coverage within the scope of 450 m is 58% and consists of 460491 people, and the percentage of the city’s population inside the area of service coverage is 42% and consists of 326720 people. The results of optimal location allocation show that service coverage is higher compared to the current sites and covers a larger number of people. The percentage of people outside the service coverage area within the scope of 450 m is 31% and consists of 243044 people, and the percentage of people who are inside the service coverage area is 69% and consists of 544167 people. The percentage of increase after implementing the recommended optimal site reached 11%.